The Influence of Work Discipline and Workload on the Performance of Public Infrastructure and Facilities Handling (PPSU) Employees with Organizational Commitment as a Mediating Variable in Subdistricts of West Jakarta Regional - Sutarman, Novia Nila; Elmi, Farida (Indonesian Journal of Business Analytics, 2024)
This research aims to test the hypothesis regarding the influence of independent variables (Work Discipline, Work Load, and Organizational Commitment) on the dependent variable (Employee Performance) in the West Jakarta Regional Subdistrict. This research uses quantitative research with a population of 50 employees and data management using SmartPLS 4. The author concludes that: (1) Work Discipline has a positive and significant effect on Organizational Commitment. (2) Workload has a negative and significant effect on Organizational Commitment. (3) Work Discipline has a positive and significant effect on Work Discipline. (4) Workload has a negative and significant effect on employee performance. (5) Organizational Commitment has a positive and significant effect on Employee Performance. (6) Work Discipline has a positive and significant effect on Employee Performance through Organizational Commitment. (7) Workload has a negative and significant effect on employee performance through organizational commitment.